Sea surface temperature variation linked to elemental mercury concentrations measured on Mauna Loa - F. Carbone; M. S. Landis; C. N. Gencarelli; A. Naccarato; F. Sprovieri; F. De Simone; I. M. Hedgecock; N. Pirrone (Geophysical Research Letters)
Abstract The Hg0 time series recorded at the Mauna Loa Observatory (MLO) in Hawaii between 2002 and 2009 has been analyzed using Empirical Mode Decomposition. This technique has been used in numerous contexts in order to identify periodical variations in time series data. The periodicities observed in the tropical Pacific sea surface temperature (SST), through the data collected from five buoys, are also observed in Hg0 concentrations and the relative humidity measured at the MLO. The lag times in the observed periodicities are related to the position of the buoys with respect to the measurement site. This demonstrates a direct link between climatological phenomena, in this case SST, and measured Hg0 and reflects the influence of ocean SST on Hg0 evasion. This is the first long‐term experimental evidence of such a direct effect on Hg0 evasion from the oceanic surface driven by temperature.